2021
DOI: 10.21608/ejhc.2021.144291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shaker Exercise on Dysphagia Level among Patients with Cerebral Vascular Stroke

Abstract: Background: Dysphagia is one of the major post-stroke complications that can severely damage patient's quality of life and even endangers patients' lives. Shaker exercise is one of the indirect methods, behavioral swallowing techniques, may increase the swallowing speed and sensitivity. The aim of the study was to evaluate the effect of Shaker exercise on dysphagia level among patients with cerebral vascular stroke. Study design: A quasi-experimental design was utilized to achieve this aim. Setting: This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Regarding the marital status; the current study reported that most of the studied patients were married. Similar to that finding, El Sayed & Ewees (12) found in their Egyptian study that most of their studied subjects were married. This finding disagreed with Abd-Elraziek et al (13) who stated that about half of their subjects were married and the others were among divorced or widow status.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the marital status; the current study reported that most of the studied patients were married. Similar to that finding, El Sayed & Ewees (12) found in their Egyptian study that most of their studied subjects were married. This finding disagreed with Abd-Elraziek et al (13) who stated that about half of their subjects were married and the others were among divorced or widow status.…”
Section: Discussionsupporting
confidence: 86%
“…This finding matched with study done by Vaish et al (14) in India who reported that nearly less than half of the studied elderly were illiterate. On the contrary, a study conducted in Egypt by El Sayed & Ewees (12) who showed that most of studied sample were read and write. Also, Hammond & Wilson (15) in Iran who found that 39% of their subjects had secondary education.…”
Section: Discussionmentioning
confidence: 87%
“…in theory, the ability to swallow or dysphagia in post-stroke patients or stroke patients is something that often occurs, one of the interventions that is very useful to improve the recovery of patients' swallowing ability is with shaker exercise. 6 Shaker exercise has a good effect, especially for stroke patients, shaker exercise is effective in activating the suprahyoid muscles including the digastric muscles, geniohyoid muscles, and mylohyoid muscles which are located at the front of the neck, besides shaker exercise can increase anterior and superior movements and contribute to opening upper esophageal sphincter in elderly individuals and patients with various diseases. 7 The results of the research by Renny Chaidir, et al in 2020 stated that the results of this study concluded that swallowing exercises can improve the swallowing ability of stroke patients with dysphagia.…”
Section: Distribution Of Pretest and Posttest Shaker Exercise Results...mentioning
confidence: 99%
“…Therapeutic modalities provided One type of exercise that can motivate the stimulation of the suprahyoid muscle and contribute to increasing the stimulation of the meineilan muscle is the shaker exercise. 6 The additional research carried out by Eiast-Eirling made the Shaker exercise effective in activating the suprahyoid muscles including the digastric, geniohyoid muscle, and mylohyoid muscles which are located in the front of the leather, SEi can increase anterior and superior movement along with beer. contribution to sphincter development Upper esophageal in elderly individuals and patients with various diseases.…”
Section: Introductionmentioning
confidence: 99%